School Committee Strategy to Improve The Quality of Education at MI Ma'arif Munggung 1, Pulung, Ponorogo - M. Suyudi; Miftahul Janah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2020)
This study aims to reveal the roles and strategies of the school committee in developing the quality of education. This research is important to do because the issue of the quality of education in Indonesia is looking for an ideal formulation due to the impact of industry 4.0. The quality of education is required to be comparable and parallel to the development of modern science. This research was conducted at Madrasah Ibtidaiyah Ma'arif 1 Munggung. At least, this research wants to find answers to how strategies to optimize the development of education quality and the role of the school committee in achieving the mission of developing educational quality. This research is qualitative. To obtain complete data and pay attention to the relevance of the data for the study, the data collection in this study used interview, observation, and documentation techniques. The collected data were analyzed using the analysis technique of Milles and Huberman. The results of this study were 1) efforts of improving quality of education in MI Ma'arif 1 Munggung among other things are improving the achievement of the school, strengthening the role of the committee, and improving the professionalism of teachers. 2) The role of the School Committee in improving the quality of education at MI Ma'arif Munggung 1 is as: a) Advisory agency, b) Supporting agency, c) Controlling agency, d) Mediator, 3) The strategies used by the School Principal in enhancing the role of School 3 Committees are: Building trust in stakeholders, building a sense of kinship with stakeholders, giving authority to committed people.